AS composition as well as preparation method and application thereof

By adding characteristic viscosity PBAT resin, styrene elastic body, chloride polyethylene, etc. to the AS composition, optimize the flame retardant performance and mechanical properties of the composition, solve the insufficient GWIT and mechanical performance of the existing materials The problem of goodness realizes the combination of high burning wire -filled temperature and good mechanical properties.

CN119371757AActive Publication Date: 2025-01-28KINGFA SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411512812.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The glow wire ignition temperature (GWIT) of existing household appliance housing materials cannot reach 775℃, and the mechanical properties are poor, which cannot meet the needs of polymer materials in household appliance housing applications.

Method used

通过在AS组合物中加入特性粘度为1.85~2.85 dl/g的PBAT树脂、苯乙烯类弹性体、氯化聚乙烯、阻燃剂、阻燃协效剂、抗滴落剂和阻燃填充物,优化组合物的阻燃性能和力学性能。

Benefits of technology

The GWIT of the AS composition reaches 775 ° C or more, with good toughness and strength, and is suitable for preparation of components that require high intensity, toughness and high -burning wire to ignite the temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105892940000021
    Figure BDA0005105892940000021
  • Figure BDA0005105892940000091
    Figure BDA0005105892940000091
  • Figure BDA0005105892940000101
    Figure BDA0005105892940000101
Patent Text Reader

Abstract

The invention relates to an AS composition as well as a preparation method and application thereof. The AS composition comprises the following components: AS resin, a flexibilizer, PBAT resin, a flame retardant, a flame retardant synergist, a flame retardant filler and an anti-dripping agent. The AS composition provided by the invention has high glowing filament light-off temperature and good toughness and strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically, to an AS composition and a preparation method and application thereof. Background Art

[0002] The housings of household appliances such as dishwashers, microwave ovens, dehumidifiers and heaters require materials with good strength, good toughness and a high glow wire ignition temperature (GWIT).

[0003] Among them, for GWIT, the International Electrotechnical Commission standard IEC 60335-1 stipulates that for unattended electronic and electrical equipment, the GWIT of materials within 3mm of or in direct contact with conductive parts with a current greater than 0.2A should be ≥775℃. This standard is one of the important standards for electronic products exported to the European market.

[0004] Common materials for household appliance casings include ABS, HIPS and ABS alloys: ABS and HIPS have good processing performance and high cost performance, but their GWIT is usually only 675-700°C; among ABS alloy materials, only PC / ABS alloy has a slightly higher GWIT, which can usually reach 725-800°C, but its fluidity is poor and its cost is high.

[0005] The Chinese patent entitled "An ABS composite material and its preparation method" adds halogen flame retardants and inorganic fillers to ABS to improve the GWIT of the material. However, the addition of a large amount of halogen flame retardants and inorganic fillers will deteriorate the toughness of the material, which will have certain limitations on the application of the material in the casing of household appliances.

[0006] Therefore, it is necessary to develop materials with GWIT ≥ 775°C and good toughness and strength to meet their application in scenarios such as household appliance casings. Summary of the invention

[0007] The primary purpose of the present invention is to overcome the problem that the GWIT of the existing materials mentioned above cannot reach a good level and has poor mechanical properties, and to provide an AS composition.

[0008] A further object of the present invention is to provide a method for preparing the above-mentioned AS composition.

[0009] A further object of the present invention is to provide the use of the above-mentioned AS composition in the preparation of household items, electronic components, household equipment, gardening equipment, medical technology equipment, motor vehicle parts or body parts.

[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0011] An AS composition comprises the following components in parts by weight:

[0012]

[0013]

[0014] The intrinsic viscosity of the PBAT resin is 1.85 to 2.85 dl / g.

[0015] The addition of flame retardants, flame retardant synergists, anti-dripping agents and flame retardant fillers can improve the flame retardant properties of the AS composition, thereby being beneficial to the improvement of the GWIT of the AS composition.

[0016] The inventors of the present invention have found through research that the addition of a PBAT resin with a characteristic viscosity can significantly improve the GWIT of the AS composition. This is because: when the AS composition contacts the glow-wire, the addition of the PBAT resin can make the AS composition easier to melt, thereby rapidly expanding the holes formed by melting, and then allowing the AS composition to detach from the glow-wire, preventing the AS composition from continuing to degrade at high temperature to produce more flammable gases, thereby increasing the GWIT temperature of the AS composition. The regulation of the characteristic viscosity of the PBAT resin is critical. The viscosity of the AS resin is usually greater than that of the PBAT resin. If the viscosity of the PBAT resin is too small, it is not conducive to the full dispersion of the PBAT resin in the AS composition, thereby failing to achieve a good effect of increasing the ignition temperature of the glow-wire, and in addition, it will deteriorate the mechanical properties of the AS composition. If the viscosity of the PBAT resin is too large, the fluidity decreases, and the AS composition cannot be quickly melted and detached from the glow-wire when in contact with the glow-wire, and the GWIT cannot be significantly improved.

[0017] Since a certain amount of flame retardant filler is added in the present invention, the toughness of the AS composition cannot reach a good level. The inventors of the present invention further studied and found that in the case of a certain amount of flame retardant filler, the addition of styrene elastomer and chlorinated polyethylene can make the mechanical properties of the AS composition reach a good level. This is because: although the styrene elastomer itself has a good toughening effect and good compatibility with the AS resin, the presence of the flame retardant filler will still affect the dispersibility of the styrene elastomer to a certain extent, and chlorinated polyethylene is an amorphous toughening agent, which can be well dispersed in the AS composition during melt extrusion, so that the styrene elasticity and chlorinated polyethylene can maximize the toughening effect in the AS composition of the present invention, thereby improving the mechanical properties of the AS composition. In addition, chlorinated polyethylene contains halogens, and when decomposed at high temperature, it will produce gases such as hydrogen chloride, which has a certain flame retardant effect and can also improve the GWIT of the AS composition.

[0018] That is, the present invention combines styrene elastomer, chlorinated polyethylene, flame retardant, flame retardant synergist, anti-dripping agent, flame retardant filler and PBAT resin with specific intrinsic viscosity, so that the GWIT of the AS composition reaches above 775°C, has a high glow-wire ignition temperature, and has good toughness and strength.

[0019] In the present invention, the intrinsic viscosity of the PBAT resin can be measured by the Ubbelohde viscosity method with reference to GB / T 14189-2015. The specific test conditions are: a mixed solution of phenol and tetrachloroethane in a mass ratio of 1:1 is used as a solvent to prepare a solution with a mass concentration of about 0.002g / ml of PBAT resin, and the solution is measured in a constant temperature water bath at 25°C using an IV2400 automatic Ubbelohde viscometer.

[0020] In the present invention, AS resin is used as the main resin, and its content is more than 16 wt % of the AS composition.

[0021] Preferably, the AS resin has a melt flow rate of 25 to 45 g / 10 min measured at 220° C. and 10 kg.

[0022] Preferably, the melt flow rate of the AS resin measured at 220° C. and 10 kg is 25 to 40 g / 10 min. Within this melt flow rate range, the mechanical properties of the AS resin of the present invention are better.

[0023] In the present invention, the melt flow rate of the AS resin can be measured according to the standard GB / T 3682.1-2018.

[0024] Preferably, the average particle size of the rubber phase of the styrene-based elastomer of the present invention is 30 to 2000 nm.

[0025] Preferably, the rubber content of the rubber phase of the styrene-based elastomer of the present invention is 40 to 80 wt%.

[0026] Preferably, the styrene content of the rubber phase of the styrene elastomer of the present invention is 13 to 35 wt%.

[0027] Preferably, the styrene elastomer is a core-shell structure.

[0028] Preferably, the styrene elastomer is at least one of polybutadiene grafted SAN (ABS high rubber powder), acrylonitrile-EPDM rubber-styrene copolymer or methyl methacrylate-butadiene-styrene copolymer.

[0029] Preferably, the mass ratio of the styrene elastomer to the chlorinated polyethylene is 1:(1-3).

[0030] Preferably, the mass ratio of the styrene elastomer to the chlorinated polyethylene is 1:(2-3). Within this range, the obtained AS composition has better toughness and higher glow-wire ignition temperature.

[0031] Preferably, the melt flow rate of the chlorinated polyethylene measured at 180° C. and 10 kg is 5 to 30 g / 10 min.

[0032] In the present invention, the melt flow rate of chlorinated polyethylene can be measured according to GB / T 3682.1-2018.

[0033] Preferably, the chlorine content of the chlorinated polyethylene is 30-40 wt%.

[0034] In the present invention, the chlorine content of chlorinated polyethylene can be measured according to GB / T 7139-2023.

[0035] In the present invention, the intrinsic viscosity of the PBAT resin may be 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7 or 2.8 dl / g.

[0036] Preferably, the intrinsic viscosity of the PBAT resin is 2.0 to 2.3 dl / g. Within this range, the glow-wire ignition temperature of the obtained AS composition is higher.

[0037] The PBAT resin of the present invention can be obtained commercially or homemade, as long as its intrinsic viscosity meets the requirements of the present invention.

[0038] Preferably, in the PBAT resin, the repeating units derived from terephthalic acid account for 45 to 92 mol % of the sum of the repeating units derived from terephthalic acid and the repeating units derived from adipic acid.

[0039] More preferably, in the PBAT resin, the repeating units derived from terephthalic acid account for 69-81 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from adipic acid. Within this range, the toughness of the obtained AS composition is better.

[0040] The homemade process of PBAT resin can be as follows:

[0041] 1) mixing terephthalic acid and / or its ester-forming derivative, butanediol and a catalyst, and reacting at 195-220° C. for 2-4 hours to obtain an esterified product A1;

[0042] 2) mixing adipic acid and / or its ester-forming derivative, butanediol and a catalyst, and reacting at 140-180° C. for 2-3 hours to obtain an esterified product A2;

[0043] 3) The esterified product A1 and the esterified product A2 are reacted at 240-255° C. and 0-50 Pa for 90-150 min to obtain the PBAT resin.

[0044] Optionally, the amount of the catalyst in step 1) is 0.01-2% of the sum of the mass of terephthalic acid and / or its ester derivative and butanediol. The catalyst can be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound or a titanium compound, more preferably a zinc compound, an aluminum compound or a titanium compound, most preferably a titanium compound; the titanium compound can be n-butyl titanate or tetraisopropyl titanate.

[0045] Optionally, the amount of the catalyst in step 2) is 0.01-2% of the sum of the mass of adipic acid and / or its ester derivative and butanediol. The catalyst can be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound or a titanium compound, more preferably a zinc compound, an aluminum compound or a titanium compound, most preferably a titanium compound; the titanium compound can be n-butyl titanate or tetraisopropyl titanate.

[0046] Preferably, the flame retardant is a brominated flame retardant.

[0047] More preferably, the brominated flame retardant is at least one of tetrabromobisphenol A, tris(tribromophenoxy)triazine, brominated epoxy, decabromodiphenylethane, brominated polyimide, brominated polystyrene, polybrominated styrene, brominated polycarbonate or brominated polyacrylate.

[0048] Preferably, the flame retardant synergist is an antimony-containing compound.

[0049] More preferably, the antimony-containing compound is at least one of antimony pentoxide or sodium antimonate.

[0050] Preferably, the mass ratio of the flame retardant to the flame retardant synergist is (4-2):1.

[0051] Preferably, the flame retardant filler is a flame retardant filler whose surface is modified with a coupling agent.

[0052] The surface of the flame retardant filler is modified with a coupling agent, which can further improve the compatibility of the flame retardant filler with the AS resin, thereby further improving the toughness of the AS composition.

[0053] More preferably, the coupling agent is a silane coupling agent; the silane coupling agent contains at least one of an epoxy group or a base, including but not limited to at least one of 3-glycidyloxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-n-butyl-3-aminopropyltriethoxysilane or anilinemethyltriethoxysilane.

[0054] More preferably, in the flame retardant filler whose surface is modified with a coupling agent, the content of the coupling agent is 1 to 3 wt %.

[0055] More preferably, the preparation process of the flame retardant filler with a coupling agent modified on the surface is as follows: the flame retardant filler is mixed with a coupling agent to obtain the flame retardant filler with a coupling agent modified on the surface.

[0056] The flame retardant fillers commonly used in the art can be used in the present invention.

[0057] Preferably, the flame retardant filler is at least one of magnesium hydroxide, magnesium carbonate, zinc carbonate, ammonium polyphosphate, melamine polyphosphate, zinc hydroxide or melamine cyanurate.

[0058] More preferably, the flame retardant filler comprises a first flame retardant filler and a second flame retardant filler in a mass ratio of 1: (0.5-2); the initial decomposition temperature of the first flame retardant filler is 300-380°C, and the initial decomposition temperature of the second flame retardant filler is 400-460°C. The initial decomposition temperature can be measured by thermogravimetric analysis, and the specific process is: using a thermogravimetric analyzer to test, N2 atmosphere, heating rate 20°C / min, to obtain a first-order derivative curve (DTG curve), the peak of the first-order derivative curve corresponds to the maximum weight loss rate, that is, the initial decomposition temperature.

[0059] The AS composition of the present invention can have a glow-wire ignition temperature that meets the requirements by selecting a single flame-retardant filler, and further selecting a composite flame-retardant filler with different initial decomposition temperatures can make the glow-wire ignition temperature of the AS composition higher.

[0060] More preferably, the flame retardant filler has an average particle size of 1 to 18 μm.

[0061] Further preferably, the average particle size of the first flame retardant filler is 1 to 18 μm; and the average particle size of the second flame retardant filler is 1 to 6 μm.

[0062] The average particle size of the flame retardant filler can be measured according to GB / T 19077-2016.

[0063] Further preferably, the first flame retardant filler is at least one of magnesium hydroxide, magnesium carbonate, zinc carbonate, ammonium polyphosphate (average degree of polymerization greater than 100) or melamine polyphosphate.

[0064] Further preferably, the average degree of polymerization of the ammonium polyphosphate is ≥100.

[0065] Further preferably, the second flame retardant filler is at least one of zinc hydroxide or melamine cyanurate.

[0066] Preferably, the anti-drip agent includes but is not limited to polytetrafluoroethylene.

[0067] Preferably, the AS composition further comprises 0.1 to 2 parts of other auxiliary agents.

[0068] More preferably, the other auxiliary agents include but are not limited to at least one of an antioxidant, a lubricant, a weathering agent or a colorant.

[0069] Further preferably, the antioxidant includes but is not limited to at least one of a hindered phenol antioxidant or a phosphite antioxidant.

[0070] Further preferably, the lubricant includes but is not limited to at least one of an amide lubricant, a stearate lubricant, an ester lubricant or a silicone lubricant.

[0071] Further preferably, the weathering agent includes but is not limited to at least one of a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber or a hindered amine light stabilizer.

[0072] Further preferably, the colorant includes at least one of a pigment-type colorant, a dye-type colorant or a colorant having special aesthetic effects.

[0073] The preparation method of the AS composition comprises the following steps: mixing the components, melt-extruding, and granulating to obtain the AS composition.

[0074] Preferably, the temperature of the melt extrusion is 160-220°C.

[0075] Preferably, the screw aspect ratio of the melt extruder is 30 to 45:1, and the screw speed is 200 to 800 rpm.

[0076] The use of the above-mentioned AS composition in the preparation of household items, electronic components, household appliances, gardening equipment, medical technology equipment, motor vehicle components or body parts also falls within the protection scope of the present invention.

[0077] In particular, the AS composition can be used to prepare articles with good strength, good toughness and high glow-wire ignition temperature, and in particular, can be used to prepare housings of household appliances.

[0078] Preferably, the household appliance is an unattended household appliance.

[0079] More preferably, the household appliance is a dishwasher, a microwave oven, a dehumidifier or a heater.

[0080] Compared with the prior art, the present invention has the following beneficial effects:

[0081] The AS composition of the present invention has a high glow-wire ignition temperature, good toughness and strength, and is particularly suitable for preparing products that need to have good strength, good toughness and a high glow-wire ignition temperature. DETAILED DESCRIPTION

[0082] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0083] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0084] AS resin 1#: KFA-130, Liaoning Jinfa, melt flow rate 39g / 10min;

[0085] AS resin 2#: SAN NF2200, Taiwan Chemical Fiber Co., Ltd., melt flow rate 29g / 10min;

[0086] AS resin 3#: SAN 2150, INEOS Styrolution Group Ltd., melt flow rate 45 g / 10 min;

[0087] PBAT resin 1#: Homemade, the preparation process is as follows:

[0088] 1) adding terephthalic acid (PTA) and 1,4-butanediol (BDO) into an esterification reaction kettle at a molar ratio of 1:1.05, and adding a catalyst n-butyl titanate accounting for 1% of the total weight of the raw materials, and reacting at a temperature of 210° C. and normal pressure for 180 minutes to obtain an esterified product A1;

[0089] 2) adding adipic acid (AA) and 1,4-butanediol (BDO) into an esterification reaction kettle at a molar ratio of 1:1.05, and adding a catalyst n-butyl titanate accounting for 1% of the total mass of the raw materials, and reacting at a temperature of 150° C. and normal pressure for 160 minutes to obtain an esterified product A2;

[0090] 3) The two esters A1 and A2 are continuously fed into a mixer for mixing, and the ratio of the repeating units from terephthalic acid to the repeating units from succinic acid is controlled by controlling the mass flow ratio of the two esters. The reaction is carried out at a temperature of 250° C. and a pressure of 50 Pa for 110 minutes to obtain PBAT resin 1#. The intrinsic viscosity of PBAT resin 1# is 2.3 dl / g; the repeating units from terephthalic acid account for 81% of the total molar amount of the repeating units from the dibasic acid.

[0091] PBAT resin 2#: self-made, the main difference between it and PBAT resin 1# is that in step 3), the temperature is 245°C and the reaction time is 90 min. The intrinsic viscosity of PBAT resin 2# is 2.0 dl / g; the repeating units from terephthalic acid account for 81% of the total molar amount of the repeating units from the dibasic acid.

[0092] PBAT resin 3#: self-made, the main difference between it and PBAT resin 1# is that in step 3), the temperature is 255°C and the reaction time is 150 min. The intrinsic viscosity of PBAT resin 3# is 2.8 dl / g; the repeating units from terephthalic acid account for 81% of the total molar amount of the repeating units from the dibasic acid.

[0093] PBAT resin 4#: homemade, the main difference between it and PBAT resin 1# is that in step 3), the mass flow ratio of the two esters is changed, and the reaction temperature is regulated to 255°C and the reaction time is 120 min. The intrinsic viscosity of PBAT resin 4# is 2.3 dl / g; the repeating units from terephthalic acid account for 69% of the total molar amount of the repeating units from the dibasic acid.

[0094] PBAT resin 5#: homemade, the main difference between it and PBAT resin 1# is that in step 3), the mass flow ratio of the two esters is changed, and the reaction temperature is regulated to 245°C and the reaction time is 100 min. The intrinsic viscosity of PBAT resin 1# is 2.3 dl / g; the repeating units from terephthalic acid account for 91% of the total molar amount of the repeating units from the dibasic acid.

[0095] PBAT resin 6#: self-made, the main difference between it and PBAT resin 1# is that in step 3), the reaction temperature is 230°C and the reaction time is 60 min. The intrinsic viscosity of PBAT resin 6# is 1.4 dl / g; the repeating units from terephthalic acid account for 81% of the total molar amount of the repeating units from the dibasic acid.

[0096] PBAT resin 7#: self-made, the main difference between it and PBAT resin 1# is that in step 3), the reaction temperature is 265°C and the reaction time is 160 min. The intrinsic viscosity of PBAT resin 7# is 3.0 dl / g; the repeating units from terephthalic acid account for 81% of the total molar amount of the repeating units from the dibasic acid.

[0097] PBAT resin A#: A400, Zhuhai Wantong Chemical Co., Ltd., intrinsic viscosity 2.0 dl / g, repeating units from terephthalic acid account for 45 wt% of the total molar amount of repeating units from dibasic acid.

[0098] Styrene elastomer 1#: polybutadiene grafted SAN, HR-181, Kumho Petrochemical Co., Ltd., Korea

[0099] Styrene elastomer 2#: methyl methacrylate-butadiene-styrene copolymer, EM-500A, LG Chemical, South Korea;

[0100] Chlorinated polyethylene 1#: CPE135C, Hangzhou Keli Chemical Co., Ltd., chlorine content 35wt%;

[0101] Other toughening agents 1#: acrylic impact modifier, KM-355P, Dow Chemical, USA;

[0102] Flame retardant 1#: tris(tribromophenoxy)triazine, commercially available.

[0103] Flame retardant 2#: brominated epoxy, commercially available.

[0104] Flame retardant synergist: antimony trioxide, commercially available.

[0105] The first flame retardant filler 1#: magnesium hydroxide, Aitemag 12FD, Jiangsu Aitek Flame Retardant Material Co., Ltd., the initial decomposition temperature is 370℃, the particle size is D 50 1.0μm;

[0106] The first flame retardant filler 2#: ammonium polyphosphate, APP101, Shouguang Weidong Chemical Co., Ltd., the initial decomposition temperature is 306℃, the particle size is D 50 15μm;

[0107] Second flame retardant filler 1#: melamine cyanurate, MCA, Shandong Haiwang Chemical Co., Ltd., initial decomposition temperature is 424℃, particle size D 50 4μm;

[0108] Second flame retardant filler 2#: zinc hydroxide, Hubei Fangde New Materials Co., Ltd., initial decomposition temperature is 441℃, particle size D 50 5μm;

[0109] Composite flame retardant filler 1#: homemade, the process is as follows: the first flame retardant filler 1# and the second flame retardant filler 1# are mixed in a mass ratio of 1:1 to obtain flame retardant filler 1#;

[0110] Composite flame retardant filler 2#: self-made, different from flame retardant filler 1# in that: the first flame retardant filler 1# is replaced by the first flame retardant filler 2#.

[0111] Composite flame retardant filler 3#: homemade, different from flame retardant filler 1# in that the second flame retardant filler 1# is replaced by the second flame retardant filler 2#.

[0112] Anti-dripping agent: polytetrafluoroethylene, SN3201, Guangzhou Energy Innovation Materials Co., Ltd.;

[0113] Other additives 1#: Antioxidant 1010 and antioxidant 168 are mixed in a mass ratio of 1:2, and both antioxidant 1010 and antioxidant 168 are commercially available products;

[0114] Other additives 2#: lubricant, ethylene bis stearamide, commercially available.

[0115] Unless otherwise specified, the components (such as anti-dripping agent, other auxiliary agents) selected in each parallel example and comparative example are the same commercially available products.

[0116] The performance of the AS compositions provided in the embodiments and comparative examples of the present invention was measured according to the following test methods:

[0117] (1) Glow wire ignition (GWIT) temperature: according to IEC 60695-2-13 (with

[0118] 100mm*100mm*2.0mm square plate);

[0119] (2) Izod notched impact strength: in accordance with standard ISO 180 / 1A-2000 (4 mm, 23°C);

[0120] (3) Tensile strength: in accordance with standard ISO 527-2012 (50 mm / min).

[0121] The AS compositions of the examples and comparative examples of the present invention were prepared by the following preparation method:

[0122] Weigh each component according to the formula; mix the components evenly, and melt extrude and granulate them through a twin-screw extruder to obtain an AS composition. The temperatures of the twin-screw extruder from zone 1 to zone 10 are 160°C, 180°C, 190°C, 200°C, 210°C, 210°C, 210°C, 220°C and 220°C, respectively; the screw aspect ratio is 40:1; and the screw speed is 600 rpm.

[0123] Examples 1 to 16

[0124] Examples 1 to 16 provide a series of AS compositions, whose formulations are shown in Tables 1 and 2.

[0125] Table 1 Formula of Examples 1 to 8 (parts by weight)

[0126]

[0127]

[0128] Table 2 Formulas of Examples 9 to 16 (parts by weight)

[0129]

[0130]

[0131] Comparative Examples 1 to 7

[0132] Comparative Examples 1 to 7 provide a series of AS compositions, and their formulations are shown in Table 3.

[0133] Table 3 Formulas of Comparative Examples 1 to 7 (parts by weight)

[0134]

[0135] The properties of the AS compositions of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 4.

[0136] Table 4 Performance test results of AS compositions of various embodiments and comparative examples

[0137]

[0138]

[0139]

[0140] From Table 4, we can see that:

[0141] The GWIT of the AS compositions of Examples 1 to 16 can reach above 775°C, and the Izod notched impact strength can reach 15 KJ / m 2 , the tensile strength can reach above 33 MPa, indicating that the AS composition of the present invention has a high glow-wire ignition temperature, good toughness and strength.

[0142] In Comparative Example 1, PBAT resin is not added, and the GWIT of the obtained AS composition cannot reach above 775°C, and the mechanical properties are reduced relative to Example 1; the viscosity of the PBAT resin added in Comparative Examples 2 and 3 is not appropriate, and the GWIT of the obtained AS composition cannot reach above 775°C, and the mechanical properties of Comparative Example 2 are not good. In Comparative Example 4, other toughening agents are used to replace chlorinated polyethylene, and the GWIT of the obtained AS composition cannot reach above 775°C, the toughness is poor, and the tensile strength is reduced relative to Example 1. In Comparative Example 5, other toughening agents are added to replace styrene elastomers, and the toughness of the obtained AS composition is poor. In Comparative Example 6, only styrene elastomers are added, and chlorinated polyethylene is not added. The GWIT of the obtained AS composition cannot reach above 775°C, the toughness is poor, and the tensile strength is reduced relative to Example 1. In Comparative Example 7, only chlorinated polyethylene is added, and no styrene elastomer is added, and the toughness of the obtained AS composition is poor.

[0143] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An AS composition, characterized in that The composition comprises the following components in parts by weight: The intrinsic viscosity of the PBAT resin is 1.85 to 2.85 dl / g.

2. The AS composition according to claim 1, characterized in that The melt flow rate of the AS resin measured at 220° C. and 10 kg is 25 to 45 g / 10 min.

3. The AS composition according to claim 1, characterized in that The styrene elastomer is at least one of polybutadiene grafted SAN, acrylonitrile-EPDM rubber-styrene copolymer or methyl methacrylate-butadiene-styrene copolymer.

4. The AS composition according to claim 1, characterized in that The chlorine content of the chlorinated polyethylene is 30-40 wt%.

5. The AS composition according to claim 1, characterized in that In the PBAT resin, the repeating units derived from terephthalic acid account for 45 to 92 mol % of the sum of the repeating units derived from terephthalic acid and the repeating units derived from adipic acid.

6. The AS composition according to claim 1, characterized in that The flame retardant is a brominated flame retardant.

7. The AS composition according to claim 1, characterized in that The flame retardant filler is at least one of magnesium hydroxide, magnesium carbonate, zinc carbonate, ammonium polyphosphate, melamine polyphosphate, zinc hydroxide or melamine cyanurate.

8. The AS composition according to claim 1, characterized in that The AS composition further comprises 0.1 to 2 parts of other auxiliary agents.

9. The method for preparing the AS composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components, melt-extruding and granulating to obtain the AS composition.

10. Use of the AS composition according to any one of claims 1 to 8 in the preparation of household items, electronic components, household appliances, gardening equipment, medical technology equipment, motor vehicle components or body parts.

Citation Information

Patent Citations

  • ACS / PBAT alloy material and preparation method and application thereof

    CN112759897A

  • Flame-retardant ABS (acrylonitrile butadiene styrene) composite material as well as preparation and application thereof

    CN116462928A

  • ABS composite material

    WO2020108204A1